Efek Kompensasi, Gaya Kepemimpinan, dan Motivasi Pada Kepuasan Kerja Karyawan KSPPS di Kulon Progo, Yogyakarta - Burhanudin, Burhanudin; Nugroho, Wahyudi Agung (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The purpose of this study was to examine the effect of compensation on job satisfaction, to examine the effect of leadership style on job satisfaction, and to examine the effect of motivation on job satisfaction. Respondents in this study were 105 employees who worked at the Sharia Financing Savings and Loans Cooperative (KSPPS) operating in Kulon Progo district, Special Region of Yogyakarta (DIY). The data collection technique used a questionnaire, while the data analysis technique used multiple linear regression. The results showed that compensation has a positive and significant effect on job satisfaction, leadership style has a positive and significant effect on job satisfaction, and motivation has a positive and significant effect on job satisfaction.Keyword: Compensation, Job satisfaction, Leadership style, Motivation